Leading schools in challenging times : eye to the future - Jones, Bruce Anthony (Educational policy in the 21st century., 2016)
Over the past 30 years our public school system has received an unprecedented amount of attention as this concerns methods of school reform and policy strategies for bringing about this reform. During the 1980s the emphasis of school reform was on transparency through school-community partnerships. Business and philanthropy, for example, became involved with issues of schooling that was unheard of prior to this period. The 1980s also gave rise to issues of school finance and student performance that went beyond traditional views that tended to focus on finance "adequacy" to views that focused more on school finance arrangements that would lead to actual "equitable outcomes" in student performance.The 1990s witnessed the emergence of the comprehensive school reform movement whereby curriculum outsourcing occurred at rates that had never occurred before. With this movement, the role of teachers and school leaders in the creation of school curriculum diminished as school districts increasingly purchased vendor-related curriculum packages, which included teacher and leader training modules and methods of curriculum assessment. On the heels of the increasing tendency of school districts to outsource school curriculum to curriculum-vendors came a rise in demands for school accountability and school outcomes. This was particularly evident with the passage of No Child Left Behind Act (NCLB) (2001). NCLB was also developed within a political context that called for demands in the academic improvement of schools and school districts that housed historically disenfranchised students. These demands were particularly important as the nation experienced and continues to experience dramatic increases in student racial and ethnic diversity.This volume, entitled, Leading Schools in Challenging Times: Eye to the Future, discusses varying types of school leadership in the context of key topics that have been at the center of on-going school reform in the United States. These topics include challenges, opportunities and issues associated with our administrator and teacher leadership pipeline, preparation and development; leadership and school finance reform, leadership and changing student and population demographics; leadership and the role of community; issues of leadership, policy, public accountability and school performance outcomes. The authors also explicate these issues with a view to the future and the status of leadership in our public school system.